2022
DOI: 10.3390/ma15155371
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite Nanoparticles In-Situ Grown and Clustered on Reduced Graphene Oxide for Supercapacitor Electrodes

Abstract: Fe3O4 nanoparticles with average sizes of 3–8 nm were in-situ grown and self-assembled as homogeneous clusters on reduced graphene oxide (RGO) via coprecipitation with some additives, where RGO sheets were expanded from restacking and an increased surface area was obtained. The crystallization, purity and growth evolution of as-prepared Fe3O4/RGO nanocomposites were examined and discussed. Supercapacitor performance was investigated in a series of electrochemical tests and compared with pure Fe3O4. In 1 M KOH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The performance of the hydrogels was more stable and better than that reported previously in the literature. The capacitance retention (%) of Fe 2 O 3 and Fe 2 O 3 /RGO was 69.2% and 86.9% after 1000 cycles, 7 respectively, and for Fe 2 O 3 /CNT-rMGO was it was reported to be 82.5% for 1000 cycles. 35 The stability of the hydrogel electrode showed the synergistic behavior for rMGO-GG, and its stable conductivity in the paths within the hydrogel network.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The performance of the hydrogels was more stable and better than that reported previously in the literature. The capacitance retention (%) of Fe 2 O 3 and Fe 2 O 3 /RGO was 69.2% and 86.9% after 1000 cycles, 7 respectively, and for Fe 2 O 3 /CNT-rMGO was it was reported to be 82.5% for 1000 cycles. 35 The stability of the hydrogel electrode showed the synergistic behavior for rMGO-GG, and its stable conductivity in the paths within the hydrogel network.…”
Section: Resultsmentioning
confidence: 97%
“…1 Hydrogels are used in many electrical devices such as smartphones, 2 watches, 3 sensors, 4–6 and in flexible and healable electronic devices. 7 Most of the existing traditional electronic energy storage devices have problems with mechanical wear and damage, and thus, wearing the electronic devices during their routine operation and application is not possible. 8–10 In addition, most of these materials are environmentally threatening to the flora and fauna of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…GO/r-GO can be used as nanometric fillers embedded in a polymeric matrix to enhance the structural, morphological, and functional properties of the composite material [3]. In addition, these materials are suitable for electronic and energy storage applications in the form of polymergraphene composites [8]. Furthermore, nanocomposites based on GO/r-GO and inorganic nanoparticles such as Au, Ag, and Pt have attracted much attention due to their applications as catalysts, photocatalysts, electrodes, sensors, substrates for surface-enhanced Raman spectroscopy, and in biomedicine [7].…”
mentioning
confidence: 99%
“…Jiang and co-workers studied the in situ growth of Fe 3 O 4 nanoparticles as homogeneous clusters on reduced graphene oxide [8]. In fact, the results showed that Fe 3 O 4 nanoparticles, anchored on r-GO surfaces, formed nanoclusters without aggregation, and they expanded the interlayer spacing between r-GO sheets.…”
mentioning
confidence: 99%
See 1 more Smart Citation